Molecular analysis of genetic diversity among different groups of potato (Solanum tuberosum L.) - Kumar, Raj; Torres, J.S. (The Indian Journal of Genetics and Plant Breeding, 2016)
Twenty one simple sequence repeat (SSR) markers were used to develop SSR profile in 169 genotypes of potato belonging to Indian accessions, tuberosum group (Solanum tuberosum ssp. tuberosum), breeding lines, neotuberosum, andigena group and tuberosum Ã— andigena derivatives. All the 21 SSR markers showed polymorphism and were able to discriminate the genotypes studied. Molecular markers viz., STM0037, STI0012, STM1052, STM 5127, STG0001 and STI0030 were useful due to their high polymorphic information content and differentiating power. A high magnitude of genetic diversity was observed in andigena group (Solanum tuberosum ssp. andigena). Andigena accessions were also diverse from other groups of accessions as most of them formed a clear separate and distinct cluster. Tuberosum group germplasm, breeding lines, neotuberosum and Indian accessions formed a separate cluster, whereas Indian accessions were distributed widely. The Shannon Weaver diversity index for Indian accessions was higher than that of breeding lines, tuberosum germplasm, neotuberosum and tuberosum Ã— andigena accessions. These results show that comparative genetic diversity of Indian accessions is good in comparison to other tuberosum group accessions.